(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This article examines the role of artificial intelligence (AI)-based applications in learning English. It analyzes how modern digital tools powered by AI technologies enhance language acquisition, improve pronunciation, grammar skills, vocabulary development, and personalized learning experiences. The study highlights the effectiveness of AI applications in increasing student motivation and providing adaptive learning environments.